Origin and genetic diversity of leatherbacks (Dermochelys coriacea) at Argentine foraging grounds - Prosdocimi, Laura (2014)
To conduct conservation of migratory species, such as marine turtles, is important to understand the population structure throughout the entire distribution of the species. We study the genetic composition of the leatherback turtles, Dermochelys coriacea foraging in waters off Argentina by analyzing 763 bp sequences of the mtDNA control region in order to determine the nesting origin of these animals. A total of 40 samples were collected from adult leatherbacks (mean 143.5; 180–123 cm curved carapace length) captured (10%) in fisheries or encountered as strandings (90%). Based on analysis of mtDNA sequences we detected 4 haplotypes, the most common (n = 26) being DC1.1, and the other two rarer DC1.3 (n = 4), DC13.1 (n = 2), and DC1.4 (n = 1). The genetic diversity was evaluated through the haplotype (0, 3712 ± 0, 1000) and nucleotide diversities (0, 000521 ± 0, 000553). Bayesian Mixed Stock Analysis (MSA) showed that the Buenos Aires foraging leatherbacks come primarily from the West African rookeries (Ghana and Gabon, mean estimate = 69% and 14% respectively). MSA results are consistent with those from mark–recapture studies, since four leatherbacks captured in Argentinean waters were adult females that were originally tagged on the nesting beaches in Gabon, West Africa. Our findings demonstrate the connection between nesting and foraging areas in the South Atlantic and illustrate the importance of the Malvinas ecoregion to the survival of migratory marine vertebrates, such as leatherbacks.